The Interrelationship of Morphological, Reproductive, and Growth Traits in Assaf Sheep in Palestine - Medhat, W. A.; Ikram, B. S.; Muayad, S.; Naceur, M. (Faculty of Animal Science, IPB University, 2025)
This study was conducted to explore the associations between morphometric, reproductive, and growth traits of Palestinian Assaf sheep raised in the northern West Bank, Palestine. Data were collected from January to May 2025, with a total of 520 ewes sampled from 26 flocks. Studied traits (not limited to) were pelvic width (PW), chest depth (CD), body condition score (BCS), number of lambs born per birth (NLB), prolificacy (PRO), weight at first lambing (WAL), lamb birth weight (LBW), and weaning weight (WWT). Results from statistical analysis revealed strong correlations (r= 0.79; p<0.01) between NLB and PRO. PW had a positive correlation (r>0.3) with reproductive performance traits. Additionally, WWT was linked to both BCS and ADM (r= 0.45; p<0.01). It was concluded that introducing morphometric traits, mainly those indicated as body capacity and pelvic structure in breeding programs for Assaf sheep, can improve not only the performance of reproduction and milk production, but also on-farm production levels, adaptability, and multi-trait merit.